1984
DOI: 10.1152/ajprenal.1984.246.5.f627
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of escape from sodium retention during angiotensin II hypertension

Abstract: This study examined the role of increased renal arterial pressure (RAP) in renal escape from the chronic Na-retaining effects of angiotensin II (ANG II). When RAP was allowed to increase during ANG II infusion (5 ng X kg-1 X min-1), urinary Na excretion (UNaV) decreased transiently on the first day but there was no significant change in Na iothalamate space or cumulative Na balance when ANG II infusion was continued for 6 days. Mean arterial pressure (MAP) rose from 100 +/- 3 to 132 +/- 2 mmHg after 3 days and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
74
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 16 publications
9
74
0
Order By: Relevance
“…The resulting increase in natriuresis establishes a new steady state at increased body Na ϩ and water content at the expense of hypertension suggests an initial failure in balance sensitivity. 11 Other investigators showed earlier that DOCA salt increases blood pressure by increasing sympathetic nerve activity, which should increase the cardiovascular sensitivity to volume. 8 Observations from DOCA salt mice that the blood pressure increase is caused by increased peripheral vascular resistance, rather than increased cardiac output with subsequent readjustments, 12 as well as the finding that venomotor tone is increased in DOCA salt rats, 13 underscore the role of cardiovascular volume sensitivity in DOCA salt hypertension.…”
Section: Titze Et Almentioning
confidence: 95%
“…The resulting increase in natriuresis establishes a new steady state at increased body Na ϩ and water content at the expense of hypertension suggests an initial failure in balance sensitivity. 11 Other investigators showed earlier that DOCA salt increases blood pressure by increasing sympathetic nerve activity, which should increase the cardiovascular sensitivity to volume. 8 Observations from DOCA salt mice that the blood pressure increase is caused by increased peripheral vascular resistance, rather than increased cardiac output with subsequent readjustments, 12 as well as the finding that venomotor tone is increased in DOCA salt rats, 13 underscore the role of cardiovascular volume sensitivity in DOCA salt hypertension.…”
Section: Titze Et Almentioning
confidence: 95%
“…Ang II-associated pressure natriuresis appears to serve as a negative feedback system on sodium retention produced by Ang II. The physiological importance of this mechanism is illustrated by the observation that if renal perfusion was prevented from rising by a servo control device during Ang II infusion, renal sodium reabsorption continued to rise to the point of pulmonary edema (40). Even with continued Ang II infusion, release of the renal clamp led to increased urinary sodium excretion with resolution of pulmonary edema (40).…”
Section: Renal Actions Of Angiotensin IImentioning
confidence: 99%
“…The physiological importance of this mechanism is illustrated by the observation that if renal perfusion was prevented from rising by a servo control device during Ang II infusion, renal sodium reabsorption continued to rise to the point of pulmonary edema (40). Even with continued Ang II infusion, release of the renal clamp led to increased urinary sodium excretion with resolution of pulmonary edema (40). Thus, the net effect of different levels of Ang II on sodium and water excretion depends critically on the balance between the antinatriuretic actions of Ang II and the effect of increased renal perfusion pressure that tends to cause natriuresis.…”
Section: Renal Actions Of Angiotensin IImentioning
confidence: 99%
“…For example, an increase in renal perfusion pressure was essential in offsetting the sodium-retaining actions of long-term infusions of aldosterone or angiotensin II. 20 - 21 When renal perfusion pressure was prevented from increasing as hypertension developed, sodium retention continued, and in some experiments the extracellular fluid volume expansion that occurred resulted in severe circulatory disturbances such as pulmonary edema, ascites, or both. However, these studies did not quantitate the importance of renal perfusion pressure per se on renal function.…”
Section: Discussionmentioning
confidence: 99%